Factors Affecting Hospital Readiness in Pandemic Situation: A Literature Review - Jenny Latief; Syahrul Said; Kusrini S Kadar (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Literature search was performed using Ebsco Host, Pubmed, ScienceDirect and Proquest databases with inclusion and exclusion criteria in accordance with the literature objectives. Review made on articles and obtained seven research articles that qualify reviews. The research article reviewed showed that there were several factors affecting the hospitals readiness in facing the pandemic. The factors are the availability of pandemic preparedness planning system, the availability of guidelines and infection prevention and control tools, education, training or simulation in facing the pandemic, the availability of facilities (medical devices and isolation room), communication system during the pandemic, the availability of human resources and pandemic preparedness evaluation system. An assessment of the factors affecting hospital readiness in facing the pandemic was performed to identify the challenges faced by hospitals and determine further action to improve hospital readiness in facing the pandemic that might occur in the future